2004
DOI: 10.1017/s0012162204000428
|View full text |Cite
|
Sign up to set email alerts
|

Intraobserver reliability of the modified Tardieu scale in the upper limb of children with hemiplegia

Abstract: This study investigated the reliability of the modified Tardieu scale in the assessment of biceps spasticity in the upper limbs of children with hemiplegic cerebral palsy (CP). Ten children, with hemiplegic CP participated in the study: six males (mean age 9 years, SD 4 years) and four females (mean age 12 years, SD 3 years). Blinded, duplicate measures of dynamic elbow extension were performed on the hemiplegic arm at time 0 and 7 days later, using the three angular velocities described in the Tardieu scale (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 16 publications
2
38
0
1
Order By: Relevance
“…1) [21]. We have previously published details of a comparison of this upper limb model with goniometric measures with a strong correlation (r = 0.93) found between the mean elbow angle measured with the goniometer and the same angle measured by the 3D upper limb model [21].…”
Section: Upper Limb Modelmentioning
confidence: 90%
See 1 more Smart Citation
“…1) [21]. We have previously published details of a comparison of this upper limb model with goniometric measures with a strong correlation (r = 0.93) found between the mean elbow angle measured with the goniometer and the same angle measured by the 3D upper limb model [21].…”
Section: Upper Limb Modelmentioning
confidence: 90%
“…1) [21]. We have previously published details of a comparison of this upper limb model with goniometric measures with a strong correlation (r = 0.93) found between the mean elbow angle measured with the goniometer and the same angle measured by the 3D upper limb model [21]. A similar comparison of frontal and sagittal plane measures at the shoulder has also shown a good correlation (r = 0.74) between the goniometric measures and the 3D measures (unpublished laboratory data).…”
Section: Upper Limb Modelmentioning
confidence: 99%
“…Mackey et al found poor testretest reliability for Tardieu Scale measurements of elbow flexors of children with hemiplegia [21]. Ansari et al showed that the inter-rater reliability for Tardieu Scale measurements with goniometry of elbow flexors of adult patients with hemiplegia is insufficient [22].…”
Section: Introductionmentioning
confidence: 99%
“…The spastic hypertonia was assessed with the Ashworth and Tardieu scores [4,7,20]. Locomotor evolution was followed on curves established from the Gross Motor Function Measure (GMFM).…”
Section: Methodsmentioning
confidence: 99%
“…After electrophysiological checking (lower row: e and f): e Sectioning of three of the four dorsal rootlets with microscissors. f Postsectioning view Ashworth scale: 0 to 4 (from no increase in tone to the rigid limb during flexion/extension) [4,7]; Tardieu scale: 0 to 4 (from no increase in tone to inexhaustible clonus throughout the range of motion) [20,46]; GMFCS = Gross Motor Function Classification System: I to V (from least to most severely affected) [27]; NYU = New York University: I to V (from least to most severely affected) [1][2][3]; Gillette walking scale: 1 to 10 (from cannot take any steps at all to can climb stairs without difficulty) [26] by the surgery. Special attention was paid to eventual deleterious consequences of excessive reduction of spasticity on locomotive power for transfers, standing and walking.…”
Section: Methodsmentioning
confidence: 99%